DYNAMICS OF STRUCTURAL AND FUNCTIONAL ELECTROPHYSIOLOGICAL PARAMETERS OF THE HEART IN PATIENTS WITH PAROXYSMAL ATRIAL FIBRILLATION AFTER AORTIC-CORONARY BYPASS GRAFTING SIMULTANEOUS WITH RADIOFREQUENCY ABLATION OF PULMONARY VEINS OSTIUM - B. G. Iskenderov; A. F. Rakhmatullov (Российский кардиологический журнал, 2014)
Aim. Assessment of antiarrhythmic efficacy of surgical radiofrequency ablation (RFA) of pulmonary veins ostiums, performed during coronary bypass grafting (CABG) procedure, and its inflluence on structural and functional and electrophysiological parameters of the heart in patients with paroxysmal atrial fibrillation (AF).Material and methods. Into open-label clinical trial totally 116 patients included (71 male and 45 female) in the age 43 to 65 y. o. (mean age 57,6±6,4 y. o.), who underwent planned CABG plus RFA. By the data of long-term Holter monitoring of ECG after 12 months after operation we divided the patients into 2 groups: 1st group — 88 patients with stable sinus rhythm and 2nd group — 28 patients with recurrent AF episodes.Results. It was shown that in patients with paroxysmal AF in 12 months after RFA with CABG there is stable sinus rhythm in 75,9% cases (1st group). After combination treatment in both groups the values of effective refractory period of the atriums and frequency threshold of arrhythmia induction were significantly decreased, however P wave dispersion increased, and some group differences of these parameters revealed. Also, in the 1st group sinus rhythm was stabilized by a significant increase of the left ventricle diastolic function, which were significantly better than in the 2nd group.Conclusion. It was shown that combination of RFA of pulmonary veins ostiums with CABG in patients with paroxysmal AF improves structural and functional electrophysiology of the heart and therefore saves stable sinus rhythm.